Pengaruh Kemampuan Menghafal Al-Quran terhadap Prestasi Belajar Pendidikan Agama Islam: Studi Kasus di SMP Al-Furqon Madrasatul Qur an Tebuireng - Ahmad Baidowi; Moh. Solehuddin (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2021)
The Qur'an is a holy book that is easy to memorize, remember and understand. There are so many pious Salaf sayings about the virtues of learning and memorizing in childhood, especially religious education. On the basis of the above thought, this research was conducted with the aim of knowing how the ability to memorize the Qur'an affects the learning achievement of Islamic religious education at Al-Furqon Middle School, to determine the extent of the influence of the ability to memorize the Qur'an on the learning achievement of Islamic religious education. . In this study, the researcher used Ex Post Facto research with the population in grades 8 & 9 being 153 students of SMP Al-Furqon Madrasatul Qur'an Tebuireng and the sample was taken 20% of the total population of 30 students. Meanwhile, the location studied was at Al-Furqon Middle School. Then the method used in this research is to use a questionnaire and report cards. The data processing uses SPSS 16 for windows with descriptive statistics frequency data analysis. In this study used the